Patterns of lower limb reconstruction and risk factors for complications at a tertiary care center - Thapa, Kamana; Maharjan, Niran; Lamichhane, Apar; Pokharel, Pashupati Babu; Dahal, Peeyush (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Lower limb injuries constitute a significant proportion of trauma admissions in Nepal, frequently requiring complex reconstructive procedures. This study aims to identify the demographic profile of patients, injury patterns, and those undergoing lower limb reconstruction, as well as to determine the risk factors for developing complications at a tertiary trauma center in Nepal. Methods: This prospective observational study was conducted at the National Trauma Center, Kathmandu. All patients undergoing reconstructive plastic surgery for lower limb trauma by the Burns, Plastic and Reconstructive Surgery Department at the National Trauma Center were included. Data on demographics, comorbidities, mode of injury, injury site, type of injury, mechanism of injury, reconstructive procedures, and complications were collected and analyzed. Results: Eighty-five patients were included, of whom 67 (78.82%) were male and 18 (21.18%) were female. The average age was 27.97 years, with only two pediatric patients (ages 10 and 12). A total of 24 patients (28.2%) experienced complications. High-velocity injuries were significantly associated with complications, accounting for 20 out of 24 cases (83.3%), and 16(60%) had open fractures. Of those with complications, 15 patients had comorbidities, and diabetic patients had the highest number of complications, such as infection. Conclusion: Lower limb defects requiring reconstruction are mostly seen in young males. Comorbidities, especially diabetes, mode of injury, type of injury, and timing of presentation, remain the main risk factors for complications. Timely presentation and availability of reconstructive expertise are critical for limb salvage and better functional outcomes.